Educator Handbook for Designing Inclusive Entrepreneurship Courses in Higher Education - McQuillan, Deirdre; Gavigan, Sylvia; Briones, Antonio Juan; Clitan, Iulia; Milioni, Dimitra L.; Muresan, Vlad; Polykarpou, Panayiota (My University, 2022)
This handbook is developed for educators in entrepreneurship within universities and other higher education institutions. The aim of the handbook is to help underrepresented student groups within their courses. It is also useful for academics who want to develop entrepreneurship courses for specific minority groups. The notion of who underrepresented entrepreneurship students are may differ across institutions and across countries. At a global level, the OECD identifies six important cohorts: women, youth, seniors, the unemployed, immigrants, and people with disabilities (OECD, 2021)
Εγχειρίδιο εκπαιδευτικού για το σχεδιασμό μαθημάτων συμπεριληπτικής επιχειρηματικότητας στην τριτοβάθμια εκπαίδευση
Keywords: Entrepreneurship; Students; Education; Minorities